2023
DOI: 10.3390/jof9020162
|View full text |Cite
|
Sign up to set email alerts
|

Complement, but Not Platelets, Plays a Pivotal Role in the Outcome of Mucormycosis In Vivo

Abstract: Background: Mucormycetes, a heterogeneous group of fungi, induce a life-threatening disease called mucormycosis. Immune deficiencies represent a major risk factor; hence, we wanted to illuminate the role of complement and platelets in the defense against mucormycetes. Methods: Rhizopus arrhizus (Ra), Rhizopus microsporus (Rm), Lichtheimia ramosa (Lr), Lichtheimia corymbifera (Lc), Rhizomucor pusillus (Rmp), and Mucor circinelloides (Mc) spores were opsonized with human and mouse serum, and C1q, C3c, and termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…Similar to the increased susceptibility to mucormycosis observed when macrophages are depleted, neutropenia is also a risk factor associated with this disease, highlighting the pivotal role of neutrophils [ 79 , 80 ]. Accordingly, the in vivo studies developed in zebrafish larvae showed that the formation of the primary granulomas is executed by neutrophils [ 81 ].…”
Section: Genetic Manipulation In Mucorales and New...mentioning
confidence: 99%
“…Similar to the increased susceptibility to mucormycosis observed when macrophages are depleted, neutropenia is also a risk factor associated with this disease, highlighting the pivotal role of neutrophils [ 79 , 80 ]. Accordingly, the in vivo studies developed in zebrafish larvae showed that the formation of the primary granulomas is executed by neutrophils [ 81 ].…”
Section: Genetic Manipulation In Mucorales and New...mentioning
confidence: 99%